Implementation of Field Studies and Its Impact on the Quality of Islamic Religious Education at UIN Sunan Kalijaga, Indonesia - Siregar, Nursima Putri; Munastiwi, Erni; Ratnasari, Dwi; Rohinah, Rohinah (Universitas Muhammadiyah Yogyakarta, 2026)
Improving the quality of Sharia higher education is a strategic necessity in the face of the increasingly complex dynamics of globalization and scientific transformation. This research aims to analyze how the implementation of field studies can serve as an instrument to enhance the academic and professional quality of the Master of Islamic Religious Education (PAI) Program at UIN Sunan Kalijaga Yogyakarta. In particular, this study examines the relevance of field experience, learning outcomes, and quality assurance systems implemented in the postgraduate environment. The research method used is a descriptive qualitative approach with a case study design. The results showed that field studies nationally and internationally is able to strengthen three main dimensions of education quality: (1) academic competence, which is shown through the ability of students to integrate Islamic education theory with practice in the field; (2) social competence, through cross-cultural collaboration and institutions that enrich scientific perspectives; and (3) improvement of the internal quality assurance system, where the results of FS are used as reflective materials for the improvement of curriculum and learning methods.